Cocaine and the British Empire: The Drug and the Diplomats at the Hague Opium Conference, 1911–12. - Mills, James H. (Journal of Imperial & Commonwealth History, 2014)
This article will consider the reasons for the inclusion of cocaine in the Hague Opium Convention of 1912. This was the first time that the emerging international drugs regulatory system considered substances other than opiates and it was British delegates who took the initiative to include cocaine in discussions and in the final version of the agreement. Historians have tended to keep brief their accounts of this episode, seeing the British agenda on cocaine as driven primarily by their wider interests in opium, or alluding briefly to colonial anxieties about manufactured drugs. This article returns to the events of 1911–12 and argues that Britain's position on cocaine deserves greater attention. It shows that British administrations in Asia had tried to control a growing market there for the drug since the turn of the century, and that their efforts had failed. In exploring the history of these efforts, and their impacts in the early days of the international narcotics-control regime, the article suggests that imperial policies are more complex than many historians have previously acknowledged, and that it may be time for fresh thinking on the relationship between empires and drugs in modern Asia.